A comparative study of the dependency of colour measurement on surface temperature. (April 2016) - Che, Jiangning; Li, Rong; Senanayake, Muditha
Abstract : In this paper, we evaluated in depth how the spectrophotometric colour measurement of an object will respond to surface temperature change. The colorimetric variations of eight coloured ceramic tiles against temperature changes were studied. Colorimetric data measured at specific temperature were compared with data measured at about 20 °C. For each coloured ceramic tile, reflectance curves and colorimetric differences resulting from temperature differences were examined to demonstrate the exact dependency of colorimetric properties across the temperature range studied. Experimental data showed that peaks and slopes on a reflectance curve are the major impact resulting from temperature variation. Colours with lower lightness and lower chroma showed smaller colorimetric changes with change in temperature, while colour with higher lightness and chroma exhibited a distinct thermochromism and linearity changes across the temperature range. A conspicuous correlation potential between surface temperature and CIE colorimetric coordinates was observed.